The U‐shaped pattern of size‐dependent mortality and its correlated factors in a subtropical monsoon evergreen forest. (17th April 2021) - Lu, Ruiling; Qiao, Yang; Wang, Jing; Zhu, Chen; Cui, Erqian; Xu, Xiaoni; He, Yi; Zhao, Zexuan; Du, Ying; Yan, Liming; Shen, Guochun; Yang, Qingsong; et al.
Abstract: Tree mortality is an important ecological process influencing multiple functions of forest ecosystems. Previous studies have shown two basic size–mortality patterns, including a competition‐driven declining and a disturbance‐driven increasing mortality rate with tree size. Subtropical forests, which have a high species diversity and subject to frequent monsoon disturbances, are widely distributed in eastern Asia. However, the tree size–mortality pattern in the mature subtropical forests remains unclear. Here we analysed patterns of size‐dependent mortality from tree species to forest community using a 5‐year inventory data from 117 species and 163, 612 individuals in a 20‐ha forest dynamic plot in a mature subtropical monsoon evergreen forest in eastern China. To explain the spatial variability in mortality patterns, two major biotic drivers (competition and tree size) and multiple local‐scale environmental factors were further analysed. Our results showed that tree size was the best predictor of tree mortality at the scales of both species and community. A species‐level analysis identified four size–mortality patterns that are shaped by species‐specific attributes such as maximum size and life form. For 27 out of 92 species that comprised 59% of tree individuals, the relationship between size and mortality exhibited a U‐shaped pattern of a first decline followed by an increase. An overall community‐scale size‐dependent mortality also showed a U‐shaped pattern. Tree mortality was also influenced by the competition and environmental conditions, but the relative importance varied widely across tree sizes and species. The competition showed significant correlations with the mortality of small trees while the effect of environmental conditions on mortality was strongest for large trees. A principal component analysis showed that a combination of biotic and abiotic factors explained 42.3% of the spatial variation in mortality at large sizes. Synthesis . Our results reveal four identifiable size‐dependent mortality patterns that differ across diverse species, jointly leading to a U‐shaped size–mortality pattern at the community level. This finding calls for the need to establish the details of every potential size–mortality pattern with consideration of the different effects of biotic and abiotic factors on tree mortality of specific size. Abstract : Our results reveal four identifiable size‐dependent mortality patterns that differ across diverse species, jointly leading to a U‐shaped size–mortality pattern at the community level. This finding calls for the need to establish the details of every potential size–mortality pattern with consideration of the different effects of biotic and abiotic factors on tree mortality of specific size. 摘要: 树木死亡是影响森林生态系统功能的重要生态过程。以往的研究揭示了两种基本的树木大小‐死亡格局，即随着树木大小的增加，竞争驱动死亡减少和干扰驱动死亡增加。常绿阔叶林广泛分布于东亚地区，该森林生态系统一方面具有较高的物种多样性，另一方面则由于东亚季风的影响而频繁遭受台风等自然因素干扰。目前，成熟常绿阔叶林的树木大小与死亡之间呈现何种格局仍然存在争议。本文以中国东部成熟常绿阔叶林的一个20公顷长期动态监测样地为研究对象，从物种到森林群落水平对树木大小‐死亡格局及其驱动因子进行研究，并探讨了两个主要生物因子（竞争和树木大小）和多个环境因子对不同径级大小树木死亡的影响。结果表明，在物种和群落尺度上，树木大小是影响树木死亡最主要的因子。物种水平的大小‐死亡格局具有四种模式，且不同的模式与特定物种的生活型等属性有关。在该样地的92个物种中，有27个物种的树木大小‐死亡格局表现为U型，即死亡随树木大小的增加呈先下降后上升的趋势。由于这些树种在群落中的相对丰度高达59％，因此导致群落水平的树木大小‐死亡格局也表现为U型。此外，树木死亡也受到竞争和环境条件的影响，但是不同因子的相对重要性在不同径级和物种间有较大差异。竞争显著影响了小树的死亡，而环境条件对大树死亡的影响较大。主成分分析表明，生物因素和非生物因素共同解释了大树死亡空间变异的42.3％。总之，该研究提出了四种树木大小‐死亡格局的判别方法，并从物种水平解释了群落水平呈现出的U型死亡格局。本研究表明，在探究生物和非生物因素对树木死亡的影响时需考虑树木径级的差异，从而更好地理解树木大小‐死亡格局。本研究呼吁与树木死亡相关的未来研究需更加关注群落水平的树木大小与死亡关系，并充分考虑生物和非生物因素的相对贡献。